In Situ Coating of Li[Ni0.33Mn0.33Co0.33]O2 Particles to Enable Aqueous Electrode Processing. Issue 10 (21st April 2016) - Loeffler, Nicholas; Kim, Guk‐Tae; Mueller, Franziska; Diemant, Thomas; Kim, Jae‐Kwang; Behm, R. Jürgen; Passerini, Stefano
Abstract: The aqueous processing of lithium‐ion battery (LIB) electrodes has the potential to notably decrease the battery processing costs and paves the way for a sustainable and environmentally benign production (and recycling) of electrochemical energy storage devices. Although this concept has already been adopted for the industrial production of LIB graphite anodes, the performance decay of cathode electrodes based on transition metal oxides processed in aqueous environments is still an open issue. In this study, we show that the addition of small quantities of phosphoric acid into the cathodic slurry yields Li[Ni0.33 Mn0.33 Co0.33 ]O2 electrodes that have an outstanding electrochemical performance in lithium‐ion cells. Abstract : Get your coat : An entirely water‐ processed Li‐ion battery that exhibits outstanding electrochemical properties is reported. We demonstrate how the addition of phosphoric acid enables an eco‐friendly, easily scalable, and sustainable cathode electrode manufacture. The issues that still prevent green battery processing are resolved on a molecular level.